Legal issues in the rehabilitation of abandoned housing projects - Md Dahlan, Nuarrual Hilal (UUM Press, 2011)
Abandoned housing project is one of the housing problems in Peninsular Malaysia.Even though there are laws and policies provided by the Malaysian Government to control the housing industry, the abandoned housing project is still an unsettled issue for the Malaysian Government to tackle.The real victims are the purchasers themselves.There is virtually no standard common way to face the problems of abandoned housing projects.Likewise, there is no similar specific method to deal with the rehabilitation of abandoned housing projects.This is due to the fact that in every abandoned housing project and its rehabilitation, the problem and issues faced by the stakeholders vary.Thus different methods are used to deal with the problems, especially to rehabilitate the projects.If the project is not variable for rehabilitation, the project will be stalled forever without any prospects for rehabilitation, to the detriment of the purchasers.This book discusses the law and practice in rehabilitating abandoned housing project in Peninsular Malaysia.Certain suggestions are also provided in this modest book for facing the problems of abandoned housing projects and their rehabilitation in Peninsular Malaysia and for the betterment of the housing industry in Peninsular Malaysia.